The problem in historical epistemology of Ottoman-Malay world relations - Özay, Mehmet (Gerakbudaya Enterprise, 2023)
This paper challenges the historical epistemology of the relations between Ottoman and the Malay World, which were initiated in the 16th century. A significant intensity of academic studies were triggered by the calamitous event of the tsunami that hit the Indian Ocean in 2004. That ‘natural’ disaster drew both the humanitarian initiatives of the Turkish government/semi-government and civil organisations, and also academia to rediscover the earlier historical interactions. It is quite interesting that the aforementioned ventures to revive the past relations were coincidental, with the initiation of the Ottomanist worldview by some circles in Turkey. Besides that, this approach, which can be named ‘renewalism’, is somewhat related, in a reactionary way, to the early Republican epistemological stance of history as well. Instead of developing the historical epistemology through rational and critical approaches, which would lay emphasis on diverse scopes of the relationships by taking into consideration multiple actors in order to understand the past relations, the recent (Turkish) academic stance has implicitly shown a certain tendency to narrate the relations with the limitation of a superiority-inferiority dichotomy, and a one-sided power-based domination. However, the latter issue is viewed as problematic. Because studies in the field of history have certain explicit methodological weaknesses, the ventures to understand past relations with the Malay world have not produced robust results. The argument is that weaknesses in the contemporary attempts to understand and restructure the past relations could be rooted in the past itself. For that purpose, certain epistemological-based policies that the Ottomans had developed since the early 16th century to engage with the general Malay world should be scrutinised. Although this paper was intended to be a continuation of a book chapter written by the present author, it is still considered a preliminary discussion. It attempts to apply an analytical perspective so as to reach the core of the problem. This endeavour is believed to provide suggestions for better comprehension of the already established epistemological and methodological weaknesses in academic circles that have ventured into the reconstruction of the Ottoman and Malay world relations.